Utilization of Kambang Iwak Recreational Park Facilities as A Community Tourism Sport in Palembang City - Handayani, Widya; Azhari, Muhammad; Lanos, Muhsana El Cintami; Arisman, Arisman (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to determine the use of the Kambang Iwak Recreational Park as a means and infrastructure for community tourism sports in Palembang City. Kambang Iwak is one of the city parks that has an important role as a green open space as well as a place for recreation and physical activity. This research is motivated by increasing public awareness of the importance of a healthy lifestyle and the need for public spaces that can support these activities. The research uses a qualitative descriptive method with a field approach. Data collection techniques were carried out through direct observation, interviews with informants, documentation, and the distribution of questionnaires to randomly selected park visitors. The results of the study show that most people use Kambang Iwak Park for sports activities such as jogging, cycling, morning gymnastics, and other leisure activities. Park facilities such as jogging tracks, night lighting, children's play areas, and a beautiful natural atmosphere are the main supporting factors that make people feel comfortable and safe when doing activities. Respondents also stated that the park made a positive contribution to their physical and mental health. However, there are several suggestions related to improving facilities, managing cleanliness, and providing space for sports community activities